Enhancing Mediation Skills: Islamic Inheritance Law Training to Prevent Disputes among Yala’s Muslim Minority in Thailand - Suyono, Hadi; Rifan, Akhmad Arif; Nugroho, Rahmat Muhajir; Hile, Abdul Hafiz (Universitas Muhammadiyah Magelang, 2025)
This International Community Service program was initiated to address the early signs of inheritance disputes among the Muslim minority community in Yala, Thailand. The initiative aimed to enhance mediation skills through structured training in Islamic inheritance law (faraid) as a preventive strategy to reduce potential familial conflicts during the inheritance distribution process. The program employed a blended learning approach consisting of both online and offline training. The online sessions delivered foundational knowledge on Islamic inheritance principles, mediation techniques, and conflict early warning systems. The offline sessions emphasized the practical application of these materials through case analysis and role-playing exercises. Community leaders, including mosque imams and school teachers, were selected as primary participants based on their strategic roles as mediators within the local dispute resolution culture. The effectiveness of the training was evaluated using a pre-test and post-test design involving a validated mediation skills scale. The results demonstrated a statistically significant improvement in participants’ mediation competencies (t(19) = 6.413, p < 0.001), confirming the positive impact of the training intervention. Qualitative feedback further revealed improvements in participants’ empathy, neutrality, problem-solving ability, and confidence in handling inheritance disputes. Overall, the program has proven to be an effective legal empowerment initiative, contributing not only to conflict prevention but also to strengthening social harmony and resilience among a vulnerable minority group. The outcomes highlight the importance of integrating religious legal knowledge with mediation skills to support peaceful dispute resolution in culturally sensitive contexts.